Pyotr Karlovich Uslar — the Founder of Caucasian Folklore - Alla I. Alieva (Studia Litterarum, 2022)
The articles examines a hitherto understudied contribution of one of the Mountain Iberian-Caucasian languages’ researcher, corresponding member of the St. Petersburg Academy of Sciences P.K. Uslar (1816–1875), to the emergence of Caucasian folklore. The scholar studied the languages of the Caucasian highlanders, relying not only on the living speech of their native speakers, but primarily on their folklore. Since before Uslar there were no scientific records and publications of the Mountain folklore, the scientist had to be the first in the history of Kavkaz studies to record them in the original languages — Abkhazian, Chechen, Avar, Lakh, Darginsky, Lezginsky, Tabasaran, the first to publish them in these languages by means of his own alphabet, which went down in the history of Caucasus studies as “Uslarovsky” and the first to accompany them with a “double” subscript and literary translation into Russian, linguistic and folklore commentary. Uslar not only consistently adhered to the principles of recording, publishing, and commenting on folklore texts defined by him, but also clearly formulated them, laying the foundations of the textual folklore of the Mountain Caucasians, which have been followed by Caucasian folklorists. No less important is the contribution of the scientist to the study of the folklore of the Caucasian highlanders — Uslar was the first in Caucasus studies to characterize the Nart epic, animals and fairy tales, parables, anecdotes, songs, proverbs and sayings. All this together, albeit with a great delay, allows to call Uslar the founder of Caucasian folklore studies.